Recrystallization kinetics in 17Cr 1Mo ferritic steel - Mungole M.N.; Trivedi P.C.; Sharma S.; Sharma R.C. (My University, 2025)
The recrystallization kinetic of 17Cr 1Mo ferritic steel was studied using 60% cold rolled samples. The recrystallization was carried out at 750, 800 and 900°C for 3, 5, 15, 30 and 60 minuets. The volume fraction of the recrystallized grains was used as a kinetic parameter. The magnitude of time exponent "n" was much less than the ideal value because of the heterogeneous recrystallization. The estimated activation energy for recrystallization "Q" was more as compared to those for pure metals.